GSK3β Overexpression in Dentate Gyrus Neural Precursor Cells Expands the Progenitor Pool and Enhances Memory Skills - Jurado-Arjona, Jerónimo (J Biol Chem, 2016)
In restricted areas of the adult brain, like the subgranular zone of the dentate gyrus (DG), there is continuous production of new neurons. This process, named adult neurogenesis, is involved in important cognitive functions such as memory and learning. It requires the presence of newborn neurons that arise from neuronal stem cells, which divide and differentiate through successive stages in adulthood. In this work, we demonstrate that overexpression of glycogen synthase kinase (GSK) 3β in neural precursor cells (NPCs) using the glial fibrillary acidic protein promoter during DG development produces an increase in the neurogenic process, increasing NPCs numbers. Moreover, the transgenic mice show higher DG volume and increased number of mature granule neurons. In an attempt to compensate for these alterations, glial fibrillary acidic protein/GSK3β-overexpressing mice show increased levels of Dkk1 and sFRP3, two inhibitors of the Wnt-frizzled complex. We have also found behavioral differences between wild type and transgenic mice, indicating a higher rating in memory tasks for GSK3β-overexpressing mice compared with wild type mice. These data indicate that GSK3β is a crucial kinase in NPC physiology and suggest that this molecule plays a key role in the correct development of DG and adult neurogenesis in this region.